Problems and Prospects of the Foreign Direct Investment-based Organization in Bangladesh - Chowdhury, Rashid Ahmed; Abdullah, Mohammad Nayeem; Saha, Jyotirmoy; Tooheen, Rahat Bari (International Journal of Economics and Financial Issues, 2017)
The article examines the problems and prospects of foreign direct investment (FDI)-based organizations in Bangladesh. The article applied a mixture of statistical tools and techniques, including a stratified random sampling and a survey questionnaire to collect relevant data. The sampling frame and sample size were based on the organizations involved in FDI-based businesses in Bangladesh. Exploratory factor analysis was conducted to examine the structure and pattern of the data. Ordinal logistic regression and odds ratio were applied as well. Role of the Board of Investment along with economic freedom and the foreign investment act emerged as the most statistically significant factors which impact patterns of FDI in the country. Keywords: Economy, Foreign Direct Investment, Bangladesh JEL Classifications: E, F, G